A Multi‐Purpose Heliophysics L4 Mission. Issue 9 (9th September 2021) - Posner, A.; Arge, C. N.; Staub, J.; StCyr, O. C.; Folta, D.; Solanki, S. K.; Strauss, R. D. T.; Effenberger, F.; Gandorfer, A.; Heber, B.; Henney, C. J.; Hirzberger, J.; et al.
Abstract: The Earth‐Sun Lagrangian point 4 is a meta‐stable location at 1 AU from the Sun, 60° ahead of Earth's orbit. It has an uninterrupted view of the solar photosphere centered on W60, the Earth's nominal magnetic field connection to the Sun. Such a mission on its own would serve as a solar remote sensing observatory that would oversee the entire solar radiation hemisphere with significant relevance for protecting Moon and Mars explorers from radiation exposure. In combination with appropriately planned observatories at L1 and L5, the three spacecraft would provide 300° longitude coverage of photospheric magnetic field structure, and allow continuous viewing of both solar poles, with >3.6° elevation. Ideally, the L4 and L5 missions would orbit the Sun with a 7.2° inclination out of the heliographic equator, 14.5° out of the ecliptic plane. We discuss the impact of extending solar magnetic field observations in both longitude and latitude to improve global solar wind modeling and, with the development of local helioseismology, the potential for long‐term solar activity forecasting. Such a mission would provide a unique opportunity for interplanetary and interstellar dust science. It would significantly add to reliability of operational observations on fast coronal mass ejections directed at Earth and for human Mars explorers on their round‐trip journey. The L4 mission concept is technically feasible, and is scientifically compelling. Plain Language Summary: This work describes the advantages of placing a spacecraft at a point 60° ahead of Earth in its orbit, which offers advantages for viewing areas on the surface of the Sun that hold critical clues about solar ionizing radiation that may affect astronauts on/at the moon or on the way to and from Mars. We describe that a combination of missions ahead and behind the Earth in its orbit would provide additional benefits, even more so if injected in an orbital plane that is tilted by ∼14°. Solar remote sensing observations from these platforms would significantly improve models of the magnetic field and solar wind of the Sun and in the inner solar system, by covering more solar surface area in longitude, but also of the polar regions. This would help us better understand when solar eruptions affect the Earth's magnetosphere. Other benefits, including long‐term advance forecasting of solar activity and the understanding of dust populations in the near‐Sun environment are also discussed. An analysis of launch capabilities shows that such a mission concept, even launching both suggested missions together, is feasible. Key Points: First thorough analysis of advantages of Earth‐Sun L4 location as observation platform, and combination of L4/L5 at moderate inclination The L4 view of solar radiation hemisphere is ideal for forecasting/warning Earth‐Moon system and Mars journey of solar energetic particles Combination of L4/L5 observations would boost inner‐heliosphere solar wind modeling and validation, and long‐term solar activity forecasting